The Influence of Self-Efficacy on Teacher Performance: Literature Review - Aurellia, Sayu; Oktarianto, Luthfi (Didaktika Tauhidi: Jurnal Pendidikan Guru Sekolah Dasar, 2025)
This study aims to describe the influence of self-efficacy on teacher performance, using a literature review as a research method. Various literatures indicate that self-confidence, or what is commonly called self-efficacy, plays a significant role in teacher performance. Considering the lack of research that specifically examines various literature sources relevant to the topic of the influence of self-efficacy on teacher performance, the researcher hopes for a more specific study reference that provides a comprehensive overview of the topic, as well as providing a useful scientific contribution to teacher professional development